Oral Cannabis consumption and intraperitoneal THC:CBD dosing results in changes in brain and plasma neurochemicals and endocannabinoids in mice - Nichole Reisdorph; Katrina Doenges; Cassandra Levens; Jon Manke; Michael Armstrong; Harry Smith; Kevin Quinn; Richard Radcliffe; Richard Reisdorph; Laura Saba; Kristine A. Kuhn (BMC, 2024)
Abstract Background While the use of orally consumed Cannabis, cannabidiol (CBD) and tetrahydrocannabinol (THC) containing products, i.e. "edibles", has expanded, the health consequences are still largely unknown. This study examines the effects of oral consumption of whole Cannabis and a complex Cannabis extract on neurochemicals, endocannabinoids (eCB), and physiological parameters (body temperature, heart rate) in mice. Methods In this pilot study, C57BL/6 J mice were treated with one of the following every other day for 2 weeks: a complex Cannabis extract by gavage, whole Cannabis mixed with nutritional gel through free feeding, or purified THC/CBD by intraperitoneal (i.p.) injection. Treatments were conducted at 4 doses ranging from 0-100 mg/kg/day of CBD with THC levels of ≤ 1.2 mg/kg/day for free feeding and gavage and 10 mg/kg/day for i.p. Body temperature and heart rate were monitored using surgically implanted telemetry devices. Levels of neurochemicals, eCB, THC, CBD, and 11-OH-THC were measured using mass spectrometry 48 h after the final treatment. Statistical comparisons were conducted using ANOVA and t-tests. Results Differences were found between neurochemicals in the brains and plasma of mice treated by i.p. (e.g. dopamine, p < 0.01), gavage (e.g., phenylalanine, p < 0.05) and in mice receiving whole Cannabis (e.g., 3,4-dihydroxyphenylacetic DOPAC p < 0.05). Tryptophan trended downward or was significantly decreased in the brain and/or plasma of all mice receiving Cannabis or purified CBD/THC, regardless of dose, compared to controls. Levels of the eCB, arachidonoyl glycerol (2-AG) were decreased in mice receiving lowest doses of a complex Cannabis extract by gavage, but were higher in mice receiving highest doses compared to controls (p < 0.05). Plasma and brain levels of THC and 11-OH-THC were higher in mice receiving 1:1 THC:CBD by i.p. compared to those receiving 1:5 or 1:10 THC:CBD. Nominal changes in body temperature and heart rate following acute and repeated exposures were seen to some degree in all treatments. Conclusions Changes to neurochemicals and eCBs were apparent at all doses regardless of treatment type. Levels of neurochemicals seemed to vary based on the presence of a complex Cannabis extract, suggesting a non-linear response between THC and neurochemicals following repeated oral dosing.